2012
DOI: 10.1155/2012/924256
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination of a Natural Juvenile Hormone Isolated from a Heteropteran Insect

Abstract: Juvenile hormone (JH), which occurs in several forms in different insects, is one of the most important insect hormones. The structure of JH in Heteroptera has not been elucidated until recently, although insects in this suborder have long been used as experimental animals for JH research. Here we review the structure determination of a novel JH in a stink bug,Plautia stali, which was named juvenile hormone III skipped bisepoxide [JHSB3: methyl (2R,3S,10R)-2,3;10,11-bisepoxyfarnesoate], based on the arrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…However, only JH II and JH III were found to initiate patency through a pathway involving PKC and Na þ /K þ ATPase similar to reports in Locusta and Rhodnius, while JH I utilizes a distinct pathway involving protein kinase A and cAMP (Pszczolkowski et al, 2005(Pszczolkowski et al, , 2008. On the other hand, recent studies in the stink bug Plautia stali (Kotaki et al, 2009(Kotaki et al, , 2012 suggest that JHSB 3 , not JH I, may be the principal JH produced in hemipteran species including Rhodnius. A similar issue arises concerning studies of Rhodnius, where out of three related forms-JH I, JH II and JH III-only JH I was able to induce patency in an in vitro assay (Ilenchuk and Davey, 1987).…”
Section: Jh Signalling Through Membrane-bound Receptorssupporting
confidence: 65%
See 1 more Smart Citation
“…However, only JH II and JH III were found to initiate patency through a pathway involving PKC and Na þ /K þ ATPase similar to reports in Locusta and Rhodnius, while JH I utilizes a distinct pathway involving protein kinase A and cAMP (Pszczolkowski et al, 2005(Pszczolkowski et al, , 2008. On the other hand, recent studies in the stink bug Plautia stali (Kotaki et al, 2009(Kotaki et al, , 2012 suggest that JHSB 3 , not JH I, may be the principal JH produced in hemipteran species including Rhodnius. A similar issue arises concerning studies of Rhodnius, where out of three related forms-JH I, JH II and JH III-only JH I was able to induce patency in an in vitro assay (Ilenchuk and Davey, 1987).…”
Section: Jh Signalling Through Membrane-bound Receptorssupporting
confidence: 65%
“…The most common JH among insects is JH III (methyl 10,11-epoxyfarnesoate), while Lepidoptera possess JH 0, JH I and JH II as well as JH III (Baker, 1990;Furuta et al, 2013;Schooley et al, 1984). In Hemiptera, the compound JH skipped bisepoxy ( JHSB 3 ) appears to be the predominant JH (Kotaki et al, 2009(Kotaki et al, , 2012. 4.1).…”
Section: Jh Chemistrymentioning
confidence: 99%
“…13 Among the seven major forms identified based on the side chain length and epoxidation position (JH 0, JH I, JH II, JH III, 4-methyl-JH I, JHB 3 , and JHSB 3 ), juvenile hormone III (JH III) is the most widely distributed insect homologue. 14 In nature, two absolute JH III optical enantiomers configurations exist: the R (R-JH III) and S (S-JH III) stereoisomers. 15−18 However, according to Yi et al, only R-JH III without S-JH III has been reported in 26 insects.…”
Section: Introductionmentioning
confidence: 99%
“…JH is synthesized in and secreted from the corpora allata . Seven different JHs in insects have been confirmed, and JH plays a crucial role in the metamorphosis, caste differentiation, and migration of insects . They also regulate vitellogenesis, reproduction, and ovary development .…”
Section: Introductionmentioning
confidence: 99%